An Analytical Study of Flexible Pavement With or Without Geo-textile - Francis, Lau Ngee Sieng (Universiti Malaysia Sarawak, (UNIMAS), 2004)
The study presents an analytical study of flexible pavement with or without geo-textile and to analyze or determine the increase in the performance of pavement using geo-textile. It has been hypothesized that in the absence of a geo-textile, intermixing between base course and sub-grade may occur. By providing geo-textile, sub-base and sub-grade can be prevented from intermixing. Consequently, it will increase structural capacity of flexible pavement. To evaluate the increased performance of flexible pavement with geo-textile, a finite element (FE) response model has been developed to describe stress and displacement response parameters for geo-textile-reinforced flexible pavement systems, where the geotextile is placed between sub-base and sub-grade layer. Two-dimensional isoparametric elements, which are consisting of eight-node quardrilateral, have been developed and applied to stress and deflection analysis. A Fortran program is developed in the study to overcome the computational burden imposed by the requirement of a deep bottom boundary in the finite element analysis of pavements. Stress and displacement have been calculated for both flexible pavements with and without geo-textile. The results calculated for both type of pavements are compared in order to determine for an increasing in the performance of pavement using geo-textile. Based on the results obtained, it showed that there is a small reduction in stress and displacement generated in the flexible pavement using geo-textile.